Komunitas ikan karang di Pantai Malalayang dan Pantai Meras Teluk Manado - Sumual, Sarah S.; Kusen, Janny D.; Warouw, Veibe; Paruntu, Carolus P.; Roeroe, Kakaskasen A.; Boneka, Farnis B. (Universitas Sam Ratulangi, 2018)
The study aimed to identify species of reef fishes, to obtain indexes of diversity and dominance, eveness and to analyze the comparison of communities between the two study sites by Sorensen similarity index. Data was gathered in-situ with underwater recordings at a depth of 6 meters assisted by diving apparatus, and using fish visual census method. Subsequent data were identified using fish identifikaction guide and WoRMS (Word Register of Marine Science) online identification applications. The number of species and specimens of reef fishes from each study site after bein identified were then analyzed the diversity, dominance and similarity of the community between the two study sites. The coral reef fishes identification results that obtained from each study site were: 20 families, 86 spesies and 362 specimen at Malalayang beach, and 15 families, 55 spesies and 217 specimen at Meras beach. The value of the calculated index o community structure obtained by H’ 3.42 (Malalayang) and 2.91 (meras) has been shown the ecological condition of coral reef ecosystem which is still stable even though diversity is moderate, but inversely with low dominance value (D=0.08). The coral reef fishes in both study sites were very diverse and there was no dominant species. Eveness of community between two study sites high.The result of community similarity analysis using Sorensen Index was 49 % (<50 %) indicates that there was no community similarity of coral reef fishes between Malalayang Beach and Meras Beach which was allegedly caused by natural factors and or anthropogenic one in both research sites.Keywords : coral reef fishes community, diversity, dominance, community similarity